AN ANALYSIS OF ACCOUNTS RECEIVABLE MANAGEMENT (A STUDY ON CV ARJUNA CREATIVE, SERVICE INDUSTRY) - Muhammad Abdil Aziz (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
In a profit oriented company, accounts receivable is vital as it may boost the company’s profit making; however, a corporate collapse may occur in the case of accounts uncollectible. Thus it is highly dependent on how the company manage its accounts receivable. Every company has its own method of managing its accounts receivable due to their diverse sources of income. As such, CV Arjuna Creative, an event organizer company, has its unique accounts receivable management in which it focuses on maintaining relationship with clients instead of managing such meager accounts receivable. In addition, brokers who distribute accounts receivable risk, contribute to uniqueness of the industry. This study applies qualitative approach as it involves interviews with the director, vice director, and accounting department staff of the company, and brokers. The results of this study indicate that the company has implemented the management of accounts receivable and the internal control. However, the company deals with the absence of accounts receivable reserve, accounting software, clear task division, and board of auditors. Keywords: accounts receivable management, internal control, event organizer company